2007
DOI: 10.1159/000109363
|View full text |Cite
|
Sign up to set email alerts
|

Azo Pigments and a Basal Cell Carcinoma at the Thumb

Abstract: Basal cell carcinoma is the most common malignant neoplasm of the skin, whereas the localization at the nail unit is very rare. We report the case of a 58-year-old patient with a periungual basal cell carcinoma at the thumb. The specific feature of the reported case is the frequent exposure to fishing baits that the patient had stained with an unknown colorant. The use of chromatography, mass spectrometry and infrared spectroscopy revealed the colorant as the azo pigment Solvent Red 8. Solvent Red 8 is a wides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 23 publications
0
36
0
Order By: Relevance
“…This is also the case with KA. Engel et al [54 ]made quite an interesting observation. They reported an uncommon case of BCC of the thumb of a 58-year-old man due to an azo-pigment-containing colorant repeatedly used as a marker of fishing bait.…”
Section: Resultsmentioning
confidence: 99%
“…This is also the case with KA. Engel et al [54 ]made quite an interesting observation. They reported an uncommon case of BCC of the thumb of a 58-year-old man due to an azo-pigment-containing colorant repeatedly used as a marker of fishing bait.…”
Section: Resultsmentioning
confidence: 99%
“…Trauma could have been an inciting factor in our case, while others[28] reported a case of BCC of the nail unit in an angler who had the habit of coloring his baits with an azo dye to attract the fishes. The dye was incriminated in the causation of the carcinoma.…”
Section: Discussionmentioning
confidence: 73%
“…Male: female ratio was 1.8:1. The thumb was the most frequently affected site[568912131519242628] and the hallux was reported in five cases. [1118212227] The right middle finger was involved in three cases[41620] and both hands were affected with almost similar frequency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, only in vitro data are available to date: they show that some azo dyes, under certain circumstances (laser therapy, UV exposure), may lead to the increase of some carcinogenic substances such as 3-3′ dichlorobenzidine [22, 23]. Recently, Engel et al[ 24] showed the role of an azo dye in the development of a BCC of the thumb. However, the relevance of such data in the specific case of tattoos is not clear as we lack in vivo data [25].…”
Section: Discussionmentioning
confidence: 99%